Evolution of the central West Greenland margin and the Nuussuaq Basin: Localised basin uplift along a stable continental margin proposed from thermochronological data. (19th June 2018) - Jess, Scott; Stephenson, Randell; Brown, Roderick
Abstract: The Late Cenozoic is typically considered a time of widespread episodic tectonic uplift along the West Greenland continental margin (36–2 Ma), similar to other margins across the North Atlantic, such as Norway, East Greenland and the UK. The present study re‐examines and remodels onshore thermochronological data from central West Greenland and the Cretaceous Nuussuaq Basin, utilising a Bayesian modelling approach and new concepts related to radiation damage within apatite. These new thermal histories indicate that slow‐protracted cooling has occurred across the southern extent of the margin during the Mesozoic and Cenozoic, whereas those from within the Nuussuaq Basin display reheating through the Late Cretaceous/Palaeogene and cooling to present. Results suggest that no significant Late Cenozoic uplift has occurred along the southern margin, while cooling in the Nuussuaq Basin is consistent with events outlined in the basin's stratigraphy and implies uplift during volcanism and an isostatic response to the unroofing of the lithosphere has elevated the modern topography. These results imply significant tectonism in the region ceased by 45 Ma, yet have wider implications regarding how low temperature thermochronology data are treated and our understanding of the postrift evolution of passive margins.